2001
DOI: 10.1046/j.0022-202x.2001.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Allergic and Irritant Contact Dermatitis are Characterized by Striking Change of Iron and Oxidized Glutathione Status in Nonlesional Area of the Skin

Abstract: To assess the consequences of oxidative stress in allergic and irritant contact dermatitis, we compared the iron level, unsaturated iron-binding capacity, total iron binding capacity, the percentage saturation of iron-binding capacity, the amount of diene conjugates as well as the amounts of total glutathione, reduced glutathione, oxidized glutathione, and the oxidized glutathione/reduced glutathione ratio in skin homogenate from lesional and nonlesional skin. Lesional skin samples were obtained from positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…According to Forslind et al [11], high iron concentrations were present in the stratum granulosum and the stratum corneum layers of AD skin. This observation has recently been confirmed by Kaur et al [12], who have shown that there is a high iron content in the skin of patients with contact dermatitis. Although Forslind et al [11] and Kaur et al [12]have not determined iron in the dermis layer, our results are in a good agreement with their data.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to Forslind et al [11], high iron concentrations were present in the stratum granulosum and the stratum corneum layers of AD skin. This observation has recently been confirmed by Kaur et al [12], who have shown that there is a high iron content in the skin of patients with contact dermatitis. Although Forslind et al [11] and Kaur et al [12]have not determined iron in the dermis layer, our results are in a good agreement with their data.…”
Section: Discussionsupporting
confidence: 75%
“…Biopsies, which are invasive techniques, were used by Forslind et al [11]and Kaur et al [12]to collect iron from human skin. The microdialysis method offers two major advantages compared to biopsies: microdialysis is only slightly invasive and, in addition, does not collect proteins.…”
Section: Discussionmentioning
confidence: 99%
“…GSSG is toxic and in normal circumstances GSSG/GSH ratio in the cells is kept very low, i.e. < 0.01 in erythrocytes [24], and close to 1:10 in the skin [25][26][27]. Increased glutathione redox ratio refers to insufficient redox-control over prooxidative mecha nisms.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several previously published data indicate that antioxidants are significantly and quantitatively modified by the application of irritants or allergens (7)(8)19).…”
Section: Fig2bmentioning
confidence: 99%